IMPLEMENTASI MODEL PEMBELAJARAN LEARNING CYCLE DALAM PEMBELAJARAN BERDIFERENSIASI PADA MATA PELAJARAN IPAS KELAS IV SEKOLAH DASAR - Naitili, Cornelia Amanda; Tulle, Anggriani Apriyani; Tanggur, Fembrianus Sunario (FKIP Universitas Citra Bangsa, 2024)
The purpose of this study is to determine the implementation of the learning cycle model in differentiated learning in science and science subjects in grade IV SDK St. Joseph 2 Naikoten. The type of research used by the researcher is qualitative research using a descriptive approach. The data collection techniques used by the researcher were interviews, observations and documentation with grade IV teachers, principals and students which produced data on the implementation of the learning cycle learning model in differentiated learning in science subjects in grade IV of SDK St. Joseph 2 Naikoten. The collection instruments in this study are observation sheets, interview guidelines or question sheets. The data was analyzed using the Miles & Huberman model with the sequence of steps of data collection, data reduction, data presentation, and conclusion drawn. The validity of the data in this study is carried out by increasing research and triangulation. The results of this study show that teachers do not experience difficulties in learning the learning cycle because they already understand the learning steps according to the existing syntax. The learning cycle model is suitable for educators in learning sciences, where students learn actively and learn material meaningfully by working and thinking. The implementation of the learning cycle learning model includes planning, implementation, and evaluation as follows: a) Learning planning, teachers prepare teaching modules student worksheets, analyze subject matter, determine learning media and learning resources. b) The implementation of learning is carried out in five stages, engagement (generating interest), exploration , explanation, elaboration (development), and evaluation. c) Learning evaluation is carried out using assessment instruments such as knowledge assessment, attitude, skills, and student learning activities. So it can be concluded that the learning cycle learning model can be applied in social studies learning because it makes students motivated to learn, cooperate, be responsible, understand the material easily and can improve student learning outcomes.